FRI0317 Circulating Levels of IC3B & C3 Predicts Sle Disease Activity: The Castle (Complement Activation Signatures in Systemic Lupus Erythematosus) Study. (15th July 2016) - Kim, A.H.; Sen, D.; Strand, V.; Fu, Q.J.; Bruchas, R.; Staten, N.; Schmidt, M.; Atkinson, J.
Abstract : Background: A major unmet need in SLE is identifying a biomarker that consistently tracks with disease activity. One approach is measuring complement activation by evaluating consumption of serum C3 and C4. However, since they are acute phase reactants (1), interpretation of these levels is challenging as serum levels may not decrease until late in a disease flare (2). iC3b is a proteolytically derived molecule of C3b, and increases with complement activation. iC3b/C3 ratio measures complement consumption relative to production, which may provide for a more accurate assessment of complement activation. Objectives: We hypothesize that blood iC3b and iC3b/C3 levels will provide a more specific and reliable marker of complement activation and disease activity in SLE. Methods: 137 adult SLE patients were enrolled in this prospective observational study. The number of patient visits varied from 1 to 7 times during the study period, encompassing 376 visits. C3 and C4 were measured by nephelometry; iC3b using an investigational lateral flow assay test (Kypha, Inc, St. Louis, MO). SLE disease activity was measured using the SLEDAI 2K Responder Index-50 (S2K RI-50) instrument. Patients with active disease are considered to have a S2K RI-50 score >4. Clinically meaningful improvement is defined as a decrease in S2K RI-50 score ≥4 from prior visit, while clinically meaningful worsening is defined as an increase in S2K RI-50 score ≥4 from prior visit. Multilevel regression models were performed to examine associations with disease activity. Ordinal logistic regression models with the generalized estimating equation modeling (GEE) were used to examine associations for clinically meaningful changes since the outcome variable is ordinal (i.e. clinical deterioration, stability, and improvement). Odds ratios and 95% confidence intervals for iC3b, C3, C4, ESR, CRP, dsDNA values, prednisone usage, and race were estimated using Proc GLIMMIX and Proc GENMOD (SAS v9.4). Results: Blood levels of iC3b, C3, iC3b/C3 ratio, C4, dsDNA, ESR, and prednisone use each correlated with SLE disease activity. Multilevel multiple logistic regression analysis revealed only iC3b/C3 ratio, dsDNA levels, and prednisone use were significant predictors of disease activity (Table 1 ). To determine whether iC3b/C3 ratio can predict clinically meaningful changes in SLE disease activity, we evaluated the interpatient association between clinical deterioration, stability, and improvement and iC3b/C3 ratios. Multiple ordinal logistic regression with GEE showed that iC3b/C3 ratio, dsDNA levels, and prednisone use significantly predicted both clinically meaningful improvement and deterioration in disease activity. Conclusions: In this prospective study, blood iC3b/C3 ratios were predictive of active SLE disease. Furthermore, iC3b/C3 ratio was predictive of clinical meaningful changes in disease activity. These data warrant further investigation of iC3b/C3 ratio as a potential biomarker for disease activity in SLE. References: Gabay & Kushner, N Engl J Med. 1999;340(6):448–454. Sturfelt & Sjoholm, Int Arch Allergy Appl Immunol. 1984:75(1):75–83. Disclosure of Interest: A. Kim Grant/research support from: Rheumatology Research Foundation, Kypha Inc., Consultant for: Pfizer, Amgen, Janssen, D. Sen: None declared, V. Strand Consultant for: Kypha Inc., Abbie, Amgen, Anthera, AstraZeneca, BMS, Genentech/Roche, GlaxoSmithKline, Janssen, Lilly, MerckSerono, Novartis, Pfizer, Takeda, UCB, Q. J. Fu Consultant for: Kypha Inc., R. Bruchas Employee of: Kypha Inc., N. Staten Employee of: Kypha Inc., M. Schmidt Employee of: Kypha Inc., J. Atkinson Grant/research support from: NIH